2020
DOI: 10.4081/ejh.2020.3117
|View full text |Cite
|
Sign up to set email alerts
|

The substance P and neurokinin-1 receptor system in human thyroid cancer: an immunohistochemical study

Abstract: To develop a new therapeutic strategy against thyroid cancer (TC), the expression of both substance P (SP) and neurokinin-1 receptor (NK-1R) must be demonstrated in TC cells. This study aims to examine by immunohistochemistry, the localization of SP and the NK-1R in human TC samples (papillary, follicular, medullary, anaplastic), in metastasis and in healthy thyroid samples. SP and the NK-1R were expressed in all normal and TC samples. In healthy glands, SP was located in follicular cells (nucleus) and colloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Currently, research is focused on the prognostic and therapeutic value of emerging molecular biomarkers that may serve as a complement in clinical practice [ 7 , 8 ]. Accumulated evidence suggests that Substance P (SP)/NK-1R alterations play a key role in head and neck oncogenesis, particularly in laryngeal carcinomas and oral squamous cell carcinomas [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, research is focused on the prognostic and therapeutic value of emerging molecular biomarkers that may serve as a complement in clinical practice [ 7 , 8 ]. Accumulated evidence suggests that Substance P (SP)/NK-1R alterations play a key role in head and neck oncogenesis, particularly in laryngeal carcinomas and oral squamous cell carcinomas [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Substance P (SP), an undecapeptide belonging to the tachykinin family of peptides, is expressed throughout the entire body. 20 SP is released from nerve endings and causes biological actions, such as neurogenic inflammation, pain, mitogenesis, and regulation of the cardiovascular system. 21 A previous study showed the localization of SP by immunohistochemistry in both human thyroid cancer and in the healthy thyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…21 A previous study showed the localization of SP by immunohistochemistry in both human thyroid cancer and in the healthy thyroid gland. 20 Therefore, it is possible that such biological actions are induced by the FNA of the thyroid. On the other hand, Van den Bruel et al reported that acute thyroid swelling after FNA in a patient with medullary carcinoma caused vasodilation and blood vessel hyperpermeability due to the local release of calcitonin generelated peptide, a potent endogenous vasodilator produced by the nervous system and universally expressed by medullary thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed a few molecular markers that have allowed better understanding of the molecular mechanisms of TC, for instance, BRAF and RAS point mutations, RET/PTC and PAX8/PPAR gene rearrangements, etc [5][6][7]. In addition, the latest study found that Substance P/neurokinin-1 receptor (SP/NK-1R) system was over-expressed in TC than that in normal thyroid tissues via immunohistochemical study, which could promote the migration and invasion of cancer cells [8]. Targeting certain molecules associated with initiation and progression of TC will be a significant and promising research area.…”
Section: Introductionmentioning
confidence: 92%